Development and characterization of a scaffold-free 3D spheroid model of induced pluripotent stem cell-derived human cardiomyocytes - Beauchamp, Philippe; Ullrich, Nina D. (Tissue engineering. Part C, Methods, 2015)
Cardiomyocytes (CMs) are terminally differentiated cells in the adult heart, and ischemia and cardiotoxic compounds can lead to cell death and irreversible decline of cardiac function. As testing platforms, isolated organs and primary cells from rodents have been the standard in research and toxicology, but there is a need for better models that more faithfully recapitulate native human biology. Hence, a new in vitro model comprising the advantages of 3D cell culture and the availability of induced pluripotent stem cells (iPSCs) of human origin was developed and characterized. Human CMs derived from iPSCs were studied in standard 2D culture and as cardiac microtissues (MTs) formed in hanging drops. Two-dimensional cultures were examined using immunofluorescence microscopy and western blotting, while the cardiac MTs were subjected to immunofluorescence, contractility, and pharmacological investigations. iPSC-derived CMs in 2D culture showed well-formed myofibrils, cell-cell contacts positive for connexin-43, and other typical cardiac proteins. The cells reacted to prohypertrophic growth factors with a substantial increase in myofibrils and sarcomeric proteins. In hanging drop cultures, iPSC-derived CMs formed spheroidal MTs within 4 days, showing a homogeneous tissue structure with well-developed myofibrils extending throughout the whole spheroid without a necrotic core. MTs showed spontaneous contractions for more than 4 weeks that were recorded by optical motion tracking, sensitive to temperature and responsive to electrical pacing. Contractile pharmacology was tested with several agents known to modulate cardiac rate and viability. Calcium transients underlay the contractile activity and were also responsive to electrical stimulation, caffeine-induced Ca2+ release, and extracellular calcium levels. A three-dimensional culture using iPSC-derived human CMs provides an organoid human-based cellular platform that is free of necrosis and recapitulates vital cardiac functionality, thereby providing a new and promising relevant model for the evaluation and development of new therapies and detection of cardiotoxicity.
Gesehen am 03.08.2020